Soft Mobility and Pedestrian Networks in Urban Areas - Galderisi, Adriana; Ceudech, Andrea (TeMA - Journal of Land Use, Mobility and Environment, 2010)
By referring to the wider strategies set up, starting from the middle of the Nineties, by the European cities to promote a sustainable urban mobility and to the more recent concept of soft mobility, which generally includes pedestrian and cycling mobility, this contribution focuses on pedestrian mobility in urban areas, outlining criteria and methods for planning and designing networks of urban public open spaces, such as roads and squares, devoted to an exclusive or prevailing pedestrian use. First of all, the paper analyzes the multiple roles played by roads and squares within the cities: “axes” supporting different mobility flows, including the pedestrian ones, and in the meanwhile urban places in which different activities (commercial activities, meeting, and so on) take place. Grounding on that, the main reasons driving toward an organization of such spaces as urban networks have been outlined. Then, some guidelines and methodological elements, both for planning pedestrian networks and designing their elements taking into account the correspondence between foreseen uses and spatial features of each element, have been provided. Furthermore, the links between the pedestrian networks and the main junctions of other urban mobility networks, as well as between the first ones and the urban contexts have been stressed. Suggested guidelines and methodological elements have been applied and tested both on historical and suburban areas of the city of Naples; nevertheless they represent only a first step towards the setting up of a method for pedestrian networks planning and design in urban areas.